Dynamic effect of fiscal policy on wealth inequality: Evidence from middle-income countries - Goodness C. Aye; Nicholas M. Odhiambo (Cogent Economics & Finance, 2022)
The study examined the dynamic effect of fiscal policy on wealth inequality in middle-income countries using panel data from 2010 to 2018 and the system Generalized Method of Moments (GMM) method. Two measures of fiscal policy were considered, namely government expenses and taxes on income, profits and capital gains. GDP per capita and adult population were used as control variables. The findings of this study show that while taxes on income, profits and capital gains have a significant negative effect on wealth inequality, government expenses have no effect whatsoever on wealth inequality.
Keywords: C33; D31; E21; E62; 330; wealth inequality; fiscal policy; middle-income; dynamics